Urea Application Rate for Crop Straw Decomposition in Temperate China - Y. Wang; H. Wang; C. Gao; P. A. Seglah; Y. Bi (Applied and Environmental Soil Science)
Returning straw to the field has become the most important straw utilization method in China. The aim of this research was to study the appropriate amount of nitrogen fertilizer applied when returning the straw of three major crops (wheat, rice, and corn) to the field in areas under low to high yield levels based on the demand of nitrogen for microbial decomposition of straw. Under the condition of returning 100% straw to the field, we developed the formula for calculating the nitrogen application rate and estimated the urea application rate for the three major grain crops. The results showed that returning straws of wheat, early-season rice, middle-season rice and late-season rice, and corn to the field with urea application at the rate of about 150 kg/ha, 120～135 kg/ha, 75 kg/ha, and 75～90 kg/ha, respectively, can provide sufficient nitrogen for microbial decomposition. The urea application rate for returning 100% wheat straw to the field in Huang-Huai-Hai region, Middle-Lower Yangtze region, Loess plateau region, and Northwest arid region was 135–230 kg/ha, 110–190 kg/ha, 85–145 kg/ha, and 95–165 kg/ha, respectively. 52.5–98.5 kg/ha of urea was used for 100% early rice straw returning to the field in Middle-Lower Yangtze region and South China. In addition, the urea application rate for 100% middle-late rice straw returning to the field was 95–180 kg/ha, 100–185 kg/ha, 95–175 kg/ha, and 75–140 kg/ha, respectively. The rate of urea application for 100% corn straw returning to the field in Northeast China, Huang-Huai-Hai, Northwest arid region, and Southwest China was 60–135 kg/ha, 50–115 kg/ha, 60–135 kg/ha, and 45–105 kg/ha, respectively. The amount of nitrogen fertilizer required for the total return of crop straw is not only affected by crop straw C : N, yield per unit area, and ratio of grass to grain but also affected by straw returning mode, regional nitrogen application level, and other factors. Therefore, the amount of nitrogen fertilizer should be adjusted according to the type of cropping system, soil, and climatic conditions of the specific location. This substantial N input for stimulating straw decomposition may favor N losses with nitrate leaching and nitrous oxide emissions and hold a potential for soil N eutrophication in the long term if the level is not carefully adjusted to the N requirement of the subsequent crops and changes in soil organic matter levels.